Study Kelayakan Bisnis Inovasi pada Pendirian Usaha Roti Kukus Ala Thailand - Nida Tasri; Sigit Djalu Purwoko (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Establishing a business is the initial process in building an economic activity that involves planning, organizing, managing, and supervising all resources to achieve business goals sustainably (Suryana, 2020). Therefore, the viral food business that is currently very popular is a very profitable business opportunity. The innovation that will be carried out is also very interesting and different from the others. The innovation that we do is from the usual Thai steamed bread, the bread only uses plain bread and jam on top, but the Thai steamed bread that we will sell is Thai steamed bread with cream cheese filling in it which will definitely melt in your mouth. For our target market, all groups from children to adults can enjoy it. We have also adjusted the price to the market and it is definitely economical. With this new innovation of Thai steamed bread, we hope that it can be well received by the community. The location that we are targeting is a strategic and busy location and will most likely open many branches throughout the city of Bandung. The data analysis technique used in this study is qualitative descriptive, which is an analysis technique used to analyze aspects, aspects that are non-financial. And quantitative descriptive such as with the object of research of business feasibility studies from marketing aspects, production aspects, human resource aspects, and financial aspects and SWOT analysis. The vision is to become a provider of delicious viral snacks at economical prices but with quality.